THE DIFFERENCE IN THE CHARGE DENSITY DISTRIBUTION OF 90Zr and 92Mo NUCLEI FROM ELASTIC ELECTRON SCATTERING - kadem, sinaa fahad; Al-Rahmani, Altaf A. (Iraqi Journal of Physics, 2020)
The calculation. of the nuclear. charge. density. distributions. ρ(r) and root. mean. square. radius.( RMS ) by elastic. electron. scattering. of medium. mass. nuclei. such. as (90Zr, 92Mo) based. on the model. of the modified. shell. and the use of the probability. of occupation. on the surface. orbits. of level 2p, 2s eroding. shells. and 1g gaining. shells. The occupation probabilities of these states differ noticeably from the predictions of the SSM. We have found. an improvement. in the determination. of ground. charge. density. and this improvement. allow. more precise. identification. of (CDD) between. (92Mo- 90Zr) to illustrate the influence of the extra two protons on the charge. density. distributions and was agree. with those of experimental. data. and Hartree. – Fock. (H.F) wave. functions.